Of men and meals. (9th May 2015) - Beyer‐Westendorf, J.; Siegert, G.
Summary Rivaroxaban is increasingly used to treat patients with acute venous thromboembolism (VTE), a potentially life‐threatening condition. Because absorption of rivaroxaban decreases from nearly 100% to 66% under fasting conditions, it is recommended that VTE patients take rivaroxaban with a meal. However, this recommendation is based on preclinical pharmacokinetic (PK) studies in healthy volunteers. So far, no clinical evidence is available to support this recommendation. We describe a case of a compliant young patient who developed recurrent pulmonary embolism during rivaroxaban treatment. PK studies provided evidence that malabsorption of rivaroxaban 20 mg due to irregular intake of meals during shift work was the leading cause of recurrent pulmonary embolism. When the patient was instructed to take rivaroxaban with a regular meal, peak plasma concentrations increased from 115 to 318 ng mL−1 (+ 176%). Consequently, the importance of taking rivaroxaban with food may have a greater clinical relevance than data from preclinical PK studies suggest.